The reinforcement of craft and entrepreneurship education in senior high schools - Sugiono Sugiono; Trisno Martono; Dewi Kusuma Wardani (Intelektual Pustaka Media Utama, 2019)
This research aimed to find out the constraints occurring in the implementation of craft and entrepreneurship education. This research employed qualitative research method. The research was taken place in three schools in DKI Jakarta as the beneficiaries of entrepreneurship program grant from the government. Data was collected through interview and observation. The result of research showed the less optimum implementation of craft and entrepreneurship education. The constraints the teacher encountered in the implementation of Craft and Entrepreneurship subject were: teacher having no background of Entrepreneurship Education, No Subject Teacher Discussion (MGMP) group available and no supporting activity for Craft and Entrepreneurship subject. Therefore, this research recommended the reinforcement of entrepreneurship education learning through establishing MGMP team, teacher training, and sustainable integration of entrepreneurship subject and program.